An assessment of the availability of cavities for secondary cavity-nesting birds in certified and conventionally-logged neotropical rainforests - Schaaf, Alejandro Alberto (2020)
The high level of forest intervention and the decrease in biodiversity as a result of logging are incentives to implement forest certification schemes. Despite the advances in the results of the impact of forest certification on biodiversity, there are few studies on species with specific habits, such as cavitynesting birds. The objective of this study is to compare the impact of forest certification and conventional logging on the richness, availability (density) and dominance of potentially suitable cavity trees for secondary cavity-nesting birds in the subtropical forests of northwestern Argentina. Seven sites were selected: three control sites which were not logged for at least 40 years, one site under Forest Stewardship Council (FSC) certification, and three sites with conventional logging. The results suggest that logged forests under FSC-certification may guarantee a diversity, availability (density) and dominance of potentially suitable cavity trees for secondary cavity-nesting birds, as well as certain characteristics (such as DBH > 40 cm), similar to unlogged forests for this group of birds. Therefore, we suggest that the forests of northwestern Argentina should be managed by a scheme under forest certification so that the high levels of cavity tree species are maintained.